2021
DOI: 10.1111/cas.15096
|View full text |Cite
|
Sign up to set email alerts
|

SHARPIN regulates the development of clear cell renal cell carcinoma by promoting von Hippel‐Lindau protein ubiquitination and degradation

Abstract: Renal cell carcinoma, originating from the renal tubular epithelial cells, is the second most lethal urinary cancer. 1 Among all subtypes of RCC, clear cell type is the most common, accounting for approximately 85%-90%. 2 Although most of the incidentally detected masses are benign and low-grade, approximately 17% of all renal cancers are diagnosed with a distant metastasis. 3 Once metastasis occurs, the prognosis of ccRCC will become poor, with a median survival of only approximately 13 months and a 5-year su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Moreover, KEGG analysis was mainly concentrated on protein digestion and absorption, the cAMP signaling pathway, the calcium signaling pathway, and the Ras signaling pathway. Te abnormal function of protein digestion and absorption following NPEPL1 expression dysregulation promoted invasion, migration, and drug resistance in ccRCC [35,36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, KEGG analysis was mainly concentrated on protein digestion and absorption, the cAMP signaling pathway, the calcium signaling pathway, and the Ras signaling pathway. Te abnormal function of protein digestion and absorption following NPEPL1 expression dysregulation promoted invasion, migration, and drug resistance in ccRCC [35,36].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, KEGG analysis was mainly concentrated on protein digestion and absorption, the cAMP signaling pathway, the calcium signaling pathway, and the Ras signaling pathway. The abnormal function of protein digestion and absorption following NPEPL1 expression dysregulation promoted invasion, migration, and drug resistance in ccRCC [ 35 , 36 ]. With the in-depth understanding of the mechanism of ccRCC development, cAMP and the Ras signaling pathway played a crucial role in regulating biological behaviors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, overexpression of SHARPIN in Chinese hamster ovarian cells can promote cell migration and cell proliferation ( 25 ). At present, several gene expression analyses targeting tumor biopsy tissue are underway, and the human SHARPIN gene is upregulated in tumorigenesis in various human cancers such as breast cancer, esophageal cancer and renal cell carcinoma ( Table 1 ) ( 96 98 ).…”
Section: The Pathophysiological Functions Of Sharpinmentioning
confidence: 99%
“…Overexpression of SHARPIN leads to elevated intracellular HIF2α in patients with Renal cell carcinoma. SHARPIN can promote polyubiquitination of pVHL and thus degradation by the proteasome, which causes HIF-2α to escape the fate of ubiquitination and successfully transfer into the nucleus to control gene expression ( 98 ). Therefore, SHARPIN promotes the development of renal cell carcinoma via enhancing the degradation of the tumor suppressor pVHL.…”
Section: The Pathophysiological Functions Of Sharpinmentioning
confidence: 99%
“…Previous studies have shown that the LUBAC contributes to the regulation of numerous physiological and pathological processes, such as inflammation [ 4 ], autoimmunity [ 5 7 ], and the cell cycle [ 8 ], which are relevant to cancer progression. The LUBAC plays important roles in cancer development and progression, including those of prostate [ 9 ], renal [ 10 ], and breast cancers [ 11 ]. A previous study reported that SHARPIN facilitates HCC development [ 12 ].…”
Section: Introductionmentioning
confidence: 99%